Cognitive function in radiologically isolated syndrome - Lebrun, Christine; Blanc, Frederic; Brassat, David; Zephir, Hélène; de Seze, Jerome (Multiple sclerosis, 2010)
Background: Radiologically isolated syndrome (RIS) is characterized by patients with asymptomatic T2 hypersignals detected by brain MRI fulfilling dissemination in space criteria and is suggestive of subclinical multiple sclerosis (MS). In previous studies, it was demonstrated that visual evoked potential and cerebrospinal fluid help to identify pejorative markers in converting to MS. Objective: To date the cognitive function has never been investigated in a cohort of RIS. The objective of this study was to investigate cognitive function in a cohort of 26 RIS patients. Methods: We prospectively assessed the BCcogSEP (a French adaptation of the Brief Repeatable Battery (BRB) including eight cognitive tests) of 26 patients with RIS, compared with 26 MS patients and 26 healthy subjects matched for age, sex and level of education. Results: When comparing the three groups, the cognitive performance was significantly lower in the RIS and MS groups compared with healthy subjects for the Paced Auditory Serial Addition Test (PASAT) 3 seconds (p = 0.002), phonemic fluencies (p = 0.02), the code of the WAIS (p = 0.05), the direct (p = 0.002) or indirect (p = 0.007) digit span test, the cross-taping test (p = 0.019) and Go—No-Go (p = 0.001). When we compared RIS and MS, the cognitive performance was significantly lower in MS patients for the direct span number (p = 0.003) and cross-tapping test (p = 0.05). We did not find significant differences between the three groups for the other tests. We did not find a correlation between clinical, biological and MRI results and cognitive dysfunctions. Conclusions: This study confirms the recently developed concept of RIS patients who present similar features to MS patients. Further studies are necessary to confirm these initial results and to correlate cognitive disorders with MRI surrogate markers.